Inhibition of Ca2+ entry by capsazepine analog CIDD-99 prevents oral squamous carcinoma cell proliferation - Sun, Yuyang; Zboril, Emily K.; De La Chapa, Jorge J.; Chai, Xiufang; Da Conceicao, Viviane Nascimento; Valdez, Matthew C.; McHardy, Stanton F.; Gonzales, Cara B.; Singh, Brij B. (Frontiers in Physiology, 2022)
Oral cancer patients have a poor prognosis, with approximately 66% of patients surviving 5-years after diagnosis. Treatments for oral cancer are limited and have many adverse side effects; thus, further studies are needed to develop drugs that are more efficacious. To achieve this objective, we developed CIDD-99, which produces cytotoxic effects in multiple cancer cell lines, including oral squamous cell carcinoma (OSCC) cell lines. While we demonstrated that CIDD-99 induces ER stress and apoptosis in OSCC, the mechanism was unclear. Investigation of the Bcl-family of proteins showed that OSCC cells treated with CIDD-99 undergo downregulation of Bcl-XL and Bcl-2 anti-apoptotic proteins and upregulation of Bax (pro-apoptotic). Importantly, OSCC cells treated with CIDD-99 displayed decreased calcium signaling in a dose and time-dependent manner, suggesting that blockage of calcium signaling is the key mechanism that induces cell death in OSCC. Indeed, CIDD-99 anti-proliferative effects were reversed by the addition of exogenous calcium. Moreover, electrophysiological properties further established that calcium entry was via the non-selective TRPC1 channel and prolonged CIDD-99 incubation inhibited STIM1 expression. CIDD-99 inhibition of calcium signaling also led to ER stress and inhibited mitochondrial complexes II and V in vitro. Taken together, these findings suggest that inhibition of TRPC mediates induction of ER stress and mitochondrial dysfunction as a part of the cellular response to CIDD-99 in OSCC.